Macrofauna bentônica associada a galerias de Lepidophthalmus siriboia Felder & Rodrigues, 1993 (Decapoda: Callianassidae) em praias amazônicas - ANDRADE, Rita de Cássia Gonçalves de (2021)
This study aims to characterize the macrobenthic fauna associated with galleries of Lepidophthalmus siriboia on two beaches on the Island of Algodoal- Maiandeua (PA). Samples were collected in May (rainy season) and November (dry season) of 2019 on Beira and Caixa d’água beaches. On each beach, two sampling sub-areas were defined, one located in the high intertidal (upper zone) and other closer to the water line (lower zone). In each area, four biological and three sediment samples for granulometry and organic matter were collected using a 10 cm diameter cylindrical sampler buried 20 cm in the substrate, in addition to the density of L. siriboia was assessed using a quadrat (0,25 m²). To compare biological descriptors (richness and density) as well as abiotic variables among periods, beaches, and areas, an univariate (ANOVA, Tukey's test) and multivariate (Permanova, PCO, PCA, Simper) methods were used. The data on the abundance of L. siriboia were analyzed separately from the associated fauna and tested between periods, beaches and areas using the same treatment. A total of 26 taxa were found (excluding L. siriboia). The phylum Annelida presented the highest number of taxa (16) and was the most abundant in the both periods, areas and zones. Polychaetes Laeonereis culveri (32.9%) and Nephtys simoni (13.4%) were the most abundant organisms during the study. Thus, higher densities of L. siriboia were observed in the rainy season and in the lower zones, possibly due to the increase in finer sediment, morphodynamic characteristics, temperature and water content in the sediment. It was also found, greater richness and density of the benthic macrofauna in the dry period, which is a conspicuous characteristic feature in Amazonian beaches.